Bactericidal Effects of Diode Laser Irradiation on Enterococcus faecalis Using Periapical Lesion Defect Model. (8th August 2011) - Nagayoshi, Masato; Nishihara, Tatsuji; Nakashima, Keisuke; Iwaki, Shigetsugu; Chen, Ker-Kong; Terashita, Masamichi; Kitamura, Chiaki
Abstract : Objective . Photodynamic therapy has been expanded for use in endodontic treatment. The aim of this study was to investigate the antimicrobial effects of diode laser irradiation on endodontic pathogens in periapical lesions using an in vitro apical lesion model. Study Design . Enterococcus faecalis in 0.5% semisolid agar with a photosensitizer was injected into apical lesion area of in vitro apical lesion model. The direct effects of irradiation with a diode laser as well as heat produced by irradiation on the viability of microorganisms in the lesions were analyzed. Results . The viability of E. faecalis was significantly reduced by the combination of a photosensitizer and laser irradiation. The temperature caused by irradiation rose, however, there were no cytotoxic effects of heat on the viability of E. faecalis . Conclusion . Our results suggest that utilization of a diode laser in combination with a photosensitizer may be useful for clinical treatment of periapical lesions.